Health assessments and screening tools for adults experiencing homelessness: a systematic review - S. J. Gordon; K. Grimmer; A. Bradley; T. Direen; N. Baker; T. Marin; M. T. Kelly; S. Gardner; M. Steffens; T. Burgess; C. Hume; J. L. Oliffe (BMC, 2019)
Abstract Background Homelessness is increasing globally. It results in poorer physical and mental health than age matched people living in permanent housing. Better information on the health needs of people experiencing homelessness is needed to inform effective resourcing, planning and service delivery by government and care organisations. The aim of this review was to identify assessment tools that are valid, reliable and appropriate to measure the health status of people who are homeless. Methods Data sources: A systematic literature search was conducted in PubMed (and Medline), PsychInfo, Scopus, CINAHL and ERIC from database inception until September 2018. Key words used were homeless, homelessness, homeless persons, vagrancy, health status, health, health issues, health assessment and health screening. The protocol was registered with PROSPERO. The National Health and Medical Research Council of Australia (NHMRC) hierarchy of evidence was applied; methodological quality of included articles was assessed using the McMaster critical appraisal tools and psychometric properties of the tools were appraised using the International Centre for Allied Health Evidence Ready Reckoner. Results Diverse tools and measures (N = 71) were administered within, and across the reviewed studies (N = 37), with the main focus being on general health, oral health and nutrition. Eleven assessment tools in 13 studies had evidence of appropriate psychometric testing for the target population in domains of quality of life and health status, injury, substance use, mental health, psychological and cognitive function. Methodological quality of articles and tools were assessed as moderate to good. No validated tools were identified to assess oral health, chronic conditions, anthropometry, demography, nutrition, continence, functional decline and frailty, or vision and hearing. However, assessments of physical constructs (such as oral health, anthropometry, vision and hearing) could be applied to homeless people on a presumption of validity, because the constructs would be measured with clinical indicators in the same manner as people living in permanent dwellings. Conclusions This review highlighted the need to develop consistent and comprehensive health assessment tools validated with, and tailored for, adults experiencing homelessness.